A Radical Vote: Disputing Meanings from the Positioning of Rita Von Hunty - Rodrigo Duarte Bueno de Godoi; Ana Paula da Rosa (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies)
In this article, we analyze the meanings produced from the flows inaugurated by the positioning of drag queen and YouTuber Rita Von Hunty on the slate formed by the candidates for the Brazilian presidency Luis Inácio Lula da Silva and José Alckmin in the 2022 elections. Considering as reference the methodological approach of case studies, both media and mediatized, we seek to describe and analyze the processuality of the case, paying particular attention to the tensions evident in the space of social circulation of meanings about Rita Von Hunty’s digital practices. Guided by mediatization studies, we noticed intense flows marked by contextual political aggravation along a rupture with an imagined expectation around the influencer’s. From materials collected in flow, we noticed that the visibility tactics operated by Rita Von Hunty on digital platforms are tensioned and show that even she, the agent of the interactional circuit, is not exempt from being drawn to the center of discussions and being a point of disputes.   Resumen En este artículo, analizamos los significados producidos a partir de los flujos inaugurados por la posición de la drag queen y YouTuber Rita Von Hunty en el escenario formado por los candidatos a la presidencia de Brasil, Luis Inácio Lula da Silva y José Alckmin, en las elecciones de 2022. Tomando como referencia el enfoque metodológico de los estudios de caso, tanto mediáticos como mediatizados, buscamos describir y analizar la procesualidad del caso, prestando especial atención a las tensiones evidentes en el espacio de circulación social de significados sobre las prácticas digitales de Rita Von Hunty. Guiados por estudios de mediatización, observamos flujos intensos marcados por una agravación política contextual a lo largo de una ruptura con una expectativa imaginada en torno al influencer. A partir de los materiales recopilados en el flujo, notamos que las tácticas de visibilidad operadas por Rita Von Hunty en plataformas digitales están tensionadas y muestran que incluso ella, como agente del circuito interactivo, no está exenta de ser llevada al centro de las discusiones y ser objeto de disputas.   Palabras Clave: Mediatización; circulación; drag queen; Rita Von Hunty; prácticas digitales; plataformas